2016
DOI: 10.1093/jxb/erw175
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-induced reversibility of cadmium toxicity in rice

Abstract: HighlightRice exposed to a toxic cadmium concentration recovers from toxicity symptoms after supplementation of the medium with silicon, and transcript levels of marker genes are readjusted to that in unstressed conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 87 publications
4
52
1
1
Order By: Relevance
“…Oxidative stress is a hallmark feature of stress (Mittler, ; Apel & Hirt, ; Gill & Tuteja, ) and its reduction by Si, by upregulating antioxidant activity, is a proposed major mode of action (Liang, ; Liang et al ., , ; Zhu et al ., ; Gong et al ., ; Gunes et al ., ; Farooq et al ., ; Hasanuzzaman et al ., ; Kim et al ., ; cf. Mateos‐Naranjo et al ., ).…”
Section: Silicon and Abiotic Stress: A Proliferation Of Proposed Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a hallmark feature of stress (Mittler, ; Apel & Hirt, ; Gill & Tuteja, ) and its reduction by Si, by upregulating antioxidant activity, is a proposed major mode of action (Liang, ; Liang et al ., , ; Zhu et al ., ; Gong et al ., ; Gunes et al ., ; Farooq et al ., ; Hasanuzzaman et al ., ; Kim et al ., ; cf. Mateos‐Naranjo et al ., ).…”
Section: Silicon and Abiotic Stress: A Proliferation Of Proposed Mechmentioning
confidence: 99%
“…[Correction added after online publication 14 July 2018: 'heavy' has been deleted from the preceding sentence.] Oxidative stress is a hallmark feature of stress (Mittler, 2002;Apel & Hirt, 2004;Gill & Tuteja, 2010) and its reduction by Si, by upregulating antioxidant activity, is a proposed major mode of action (Liang, 1999;Liang et al, 2003Liang et al, , 2006Zhu et al, 2004;Gong et al, 2005;Gunes et al, 2007;Farooq et al, 2016;Hasanuzzaman et al, 2017;Kim et al, 2017;cf. Mateos-Naranjo et al, 2015).…”
Section: Silicon and Abiotic Stress: A Proliferation Of Proposed Mmentioning
confidence: 99%
“…Silicon plays several roles in metal uptake, translocation and metal binding associated with Cd tolerance in different plant species (Rogalla & Romheld ; Greger et al ; Kabir et al ). Studies have shown that high Si (1.0–1.5 m m ) is useful to mitigate Cd toxicity in rice (Farooq et al ), wheat (Greger et al ) and alfalfa (Kabir et al ). In regulating the translocation of heavy metals to the shoot, an important strategy is to create complexes between such heavy metals and other substances, such as amino acids, phytochelatins and organic acids (Sanita di Toppi & Gabbrielli ; Cho et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Si‐based resistance is reported to be associated with the production of defensive substances such as oxidative enzymes, phytoalexins, lignin and suberin, compounds that are intimately related to plant resistance against pathogen infection and herbivore attack both above‐ (Han et al., ; Ma & Yamaji, ) and belowground (Frew, Allsopp, Gherlenda, & Johnson, ). Finally, Si was reported to alleviate the negative abiotic effects of salinity (Liu et al., ), drought (Chen, Yao, Cai, & Chen, ) and heavy metal toxicity (Farooq, Detterbeck, Clemens, & Dietz, ) in plants.…”
Section: Introductionmentioning
confidence: 99%